Pathological Demand Avoidance: symptoms but not a syndrome. (June 2018) - Green, Jonathan; Absoud, Michael; Grahame, Victoria; Malik, Osman; Simonoff, Emily; Le Couteur, Ann; Baird, Gillian
Summary: Pathological (or extreme) demand avoidance is a term sometimes applied to complex behaviours in children within—or beyond—autism spectrum disorder. The use of pathological demand avoidance as a diagnosis has, at times, led to altered referral practice and misunderstandings between professionals and the families of patients. In our Viewpoint, we reviewed the current literature and conclude that the evidence does not support the validity of pathological demand avoidance as an independent syndrome. Nevertheless, the use of the term highlights an important known range of co-occurring difficulties for many children with autism spectrum disorder that can substantially affect families. We explore how these difficulties can best be understood through understanding of social, sensory, and cognitive sensitivities in autism spectrum disorder, identification of frequently occurring comorbid conditions, and assessment of how these problems interact within the child's social environment. Such understanding should then inform individualised management strategies for children and families, and in social settings, such as education. It is crucial that a shared understanding is achieved between professionals and families in this area.